Doświadczenie religijne jako subiektywne przeżywanie sacrum w teoretycznych i empirycznych odsłonach - Zaręba, Sławomir; Gawlak, Maciej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
In modern societies, unlike traditional ones, the religious interpretation of everyday life is no longer as obvious and common as it used to be. Sociologists of religion seem to agree that the spiritual identity of individuals and groups is no longer built on religious values, but more and more often on the content disseminated by modern media. It is new technologies and the digital world that transform societies, changing the optics of perception and assessment of both material and immaterial reality. Media-based content sometimes directly questions the transcendent Authority. In the context of these changes, it seems reasonable to ask about the essence and place of religious experience in the life of a contemporary individual, and about their relationship to the sacred. Hence, the key subject of this study is the dimension of religiosity – as proposed years ago by Glock and Stark – which eludes simplex, statistical analysis and description. Being strongly subjective, it pinpoints to deeper inner experiences. Religious experience – as one of the most intense human experiences, and the one known to be most difficult to research – is most often located in the area of psychological explorations. Nonetheless, it is subject to complex social conditioning as well, which makes it a legitimate object of sociological investigations. This is confirmed by the referenced theoretical and empirical orientations, which additionally prove the complexity and multidimensionality of the phenomenon under study.